2018
DOI: 10.4265/bio.23.7
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Analysis to Distinguish between Physical Decrease and Inactivation of Viable Phages in Aerosol by Quantitating Phage-Specific Particles

Abstract: Recent studies have investigated the efficacy of air-cleaning products against pathogens in the air. A standard method to evaluate the reduction in airborne viruses caused by an air cleaner has been established using a safe bacteriophage instead of pathogenic viruses; the reduction in airborne viruses is determined by counting the number of viable airborne phages by culture, after operating the air cleaner. The reduction in the number of viable airborne phages could be because of "physical decrease" or "inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Some studies on pathogen transmission from infected iments, and then nucleic acid copies-to-PFU of some viruses were calculated based on some published study and my unpublished study (Table 2) (Ueki et al 2020;Buonanno et al 2020;Shimasaki et al, 2018) . C RNA of SARS-CoV-2 with difference among these studies showed larger value than one of influenza.…”
Section: Transmission Experiments Of Viral Pathogen Between Model Ani...mentioning
confidence: 99%
“…Some studies on pathogen transmission from infected iments, and then nucleic acid copies-to-PFU of some viruses were calculated based on some published study and my unpublished study (Table 2) (Ueki et al 2020;Buonanno et al 2020;Shimasaki et al, 2018) . C RNA of SARS-CoV-2 with difference among these studies showed larger value than one of influenza.…”
Section: Transmission Experiments Of Viral Pathogen Between Model Ani...mentioning
confidence: 99%